Why Does Our Experience Start from the Middle? On Three “Meditations on the Mediated Experience” - Bosančić, Boris (Anafora, 2023)
From a particular point of view that engages in several areas of human knowledge and activity, the paper attempts to trace possible sources of our experience based on signs and their interrelationships, as well as the process of attributing meaning. The main thesis of the paper is that our experience starts from the middle, and as such, it is always mediated, either by signifiers, as suggested by Jacques Derrida’s poststructuralist theory on writing, or by the process of attributing meaning according to Heinz von Foerster’s constructivist approach to the cognitive process, or by means of the signified as an occurrence that is generated in experiments of quantum physics only by the very act of observation, presupposed by the philosophical implications of the quantum theory by Werner Heisenberg.